Nanomagnetism and Spintronics - Shinjo, Teruya Ed. (London : Elsevier, 2014)
"Spintronics is a newly developing area in the field of magnetism, in which the interplay of magnetism and transport phenomena is studied experimentally and theoretically. This book introduces the recent progresses in the research relating to spintronics."--Publishers website
Overview -- GMR, TMR, BMR, and related phenomena -- Spin injection and voltage effects in magnetic nanopillars and its applications -- Dynamics of magnetic domain walls in nanomagnetic systems -- Theoretical aspects of current-driven magnetization dynamics -- Micromagnetics of domain wall dynamics in soft nanostrips -- V-based ferromagnetic semiconductors.
Keywords: Spintronics; Nanoelectromechanical Systems; Electromagnetism